Efektivitas Game Blooket pada Model Borg and Gall terhadap Minat Belajar Siswa di MTs Hidayatul Muhajirin - Ariyani, Nili; Jasiah, Jasiah (Lembaga Yasin AlSys, 2024)
This research focuses on developing Blooket-based educational games as learning aids for Muamalah Fiqh material, aimed at class IX students at MTs Hidayatul Muhajirin. The methodology used is Research and Development (R&D) based on the Borg and Gall model. Even though this model includes ten stages, the research only utilized two main steps, namely the development stage and the implementation stage. A total of 26 class IX students were involved as participants in this research. Data was obtained by filling out a questionnaire which was distributed online using Google Form after implementing the learning media. Additionally, analysis of student feedback was conducted to gain additional insights. Based on the analysis results, it was found that the application of Blooket significantly increased students' enthusiasm for learning. The average student interest score before using this media was 65, and increased to 93 after its implementation. Students also stated that the Blooket game made the learning process more interesting and efficient. The results of this research indicate that Blooket can function as an innovative learning media that is effective in increasing learning motivation. In the future, it is hoped that this media can provide great benefits for the teaching and learning process at MTs Hidayatul Muhajirin and become an inspiration for the development of similar media.